Crusaders Against Opium : Protestant Missionaries in China, 1874-1917. - Lodwick, Kathleen L. (The University Press of Kentucky, 1996)
Opium addiction in China during the closing decades of the Ch'ing dynasty afflicted all segments of society. From government officials to farmers, the population fell prey to the effects of the drug. Some provinces reported addiction rates as high as eighty percent. With the birth of Chinese nationalism, reformers -- missionaries who had witnessed the effects of opium on Chinese society, students who had studied abroad and returned to their native land with broader perspectives, families who had lost all through the addiction of a loved one, doctors who had firsthand knowledge that opium use le.